Ammonium bicarbonate pretreatment of corn stalk for improved methane production via anaerobic digestion: Kinetic modeling. (November 2019) - He, Chao; Zhao, Junhui; Wang, Shaopeng; Guan, Shanyue; Zhang, Zhiping; Zhang, Quanguo; Pan, Xiaohui; Jiao, Youzhou
Highlights: The corn straw was pretreated with ammonium carbonate to improve biogas production. Biogas production with 8% ammonium bicarbonate (w/w) increased by 31%. The removal rate of COD with 8% ammonium bicarbonate (w/w) increased by 100%. The modified Gompertz equation fitted cumulative biogas production curves very well. Abstract: This work studied the effects of ammonium carbonate pretreatment on biogas production during sequential anaerobic digestion. The results showed that the addition of ammonium bicarbonate (8%, w/w) obtained the highest biogas production of 14, 690 mL with a yield of 222.6 mL g −1, which was 31% higher than that of un-pretreated (control experiment). Interestingly, the COD removal was increased by 100%. Furthermore, it was also helpful in stabilizing the pH of anaerobically digested corn stalk. Based on the results, the modified Gompertz equation fitted the cumulative biogas production curves very well, with high correlation coefficients (>0.994).